Visualization of complex DNA double-strand breaks in a tumor treated with carbon ion radiotherapy - Oike, Takahiro; Niimi, Atsuko; Okonogi, Noriyuki; Murata, Kazutoshi; Matsumura, Akihiko; Noda, Shin-Ei; Kobayashi, Daijiro; Iwanaga, Mototaro; Tsuchida, Keisuke; Kanai, Tatsuaki; Ohno, Tatsuya; Shibata, Atsushi; et al. (Scientific reports, 2016)
Carbon ion radiotherapy shows great potential as a cure for X-ray-resistant tumors. Basic research suggests that the strong cell-killing effect induced by carbon ions is based on their ability to cause complex DNA double-strand breaks (DSBs). However, evidence supporting the formation of complex DSBs in actual patients is lacking. Here, we used advanced high-resolution microscopy with deconvolution to show that complex DSBs are formed in a human tumor clinically treated with carbon ion radiotherapy, but not in a tumor treated with X-ray radiotherapy. Furthermore, analysis using a physics model suggested that the complexity of radiotherapy-induced DSBs is related to linear energy transfer, which is much higher for carbon ion beams than for X-rays. Visualization of complex DSBs in clinical specimens will help us to understand the anti-tumor effects of carbon ion radiotherapy.